Spider Web Shape of Brass Catalytic Converter for Reducing Exhaust Gas Emission - Roro Heni Hendaryati; Ali Mokhtar (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2017)
The rapid increase of the number of motor vehicles, especially motorcycles, makes serious problem caused by the pollution from gas emission of fossil fuel combustion. The problems related to human health and the erosion on ozone layer is credited to its gas emission. Several dangerous and toxic gasses such as Hydrocarbon (HC), Carbon Monoxide (CO), and Nitrogen Oxide (NOx), Sulphur Dioxide (SO2), and Lead (Pb) are emitted during IC engine operation.